Traditional medicine use and associated factors in chronic patients in Jamalpur, Bangladesh: a cross-sectional study - Poli, Mahmuda Akter; Hossain, Md Jamil; Kholil, Ibrahim; Yasmin, Sumaya; Bhowmick, Bishwjit; Kundu, Lakshmi Rani (Frontiers in Public Health, 2025)
BackgroundThe history of traditional medicine is extensive. While modern medicine is commonly used to treat chronic illness, traditional medicine (TM) is gaining popularity as a healthcare practice in Bangladesh. However, evidence regarding the prevalence, patterns, and associated factors of TM use among chronic illness patients in Bangladesh remains limited. This study aimed to explore the use of traditional medicine among adults with chronic illnesses.MethodsA cross-sectional study was conducted among 518 adults with chronic illness from October to December 2023. Data was collected through face-to-face interviews. The Chi-square test was used to determine the association between categorical variables and multinomial logistic regression models to identify the factors associated with the use of traditional medicine.ResultsThe mean age of the participants was 43.7 (SD = 15.9) years. Among the respondents, 8.3% used traditional medicine and 5.2% used both traditional and modern medicine. Homeopathy, herbal medicine, and ayurveda were used by 69, 23, and 9%, respectively. Bivariate analysis revealed that gender (p = 0.014), educational qualification (p = 0.010), monthly income (p < 0.001), occupation (p = 0.002) and place of residence (p < 0.001) were statistically significantly associated with traditional medicine use. Among the respondents, 22.9% of people who used traditional medicine claimed that it was effective for disease management. Multinomial logistic regression revealed that rural individuals were seven times more likely to use TM compared to urban residents(AOR = 7.545, 95% CI: 2.933, 19.412, p < 0.001).ConclusionThis study revealed that individuals living in rural areas with lower monthly incomes were more likely to use traditional medicine for the treatment of chronic illnesses. Older individuals utilized it more compared to younger ones. Additionally, the study highlighted the perceived effectiveness of traditional medicine in managing chronic illnesses. These findings emphasize the need for a collaborative healthcare approach that integrates traditional medicine with modern practices to better address the diverse needs of populations.